The Influence of Ethical Code on the Risk of Asset Misappropriation through Whistleblowing Intentions - Sielly Budi Prameswari (International Journal of Economics, Management and Accounting, 2025)
Namely, 42% of frauds are detected by complaints (tips). Research comparing theory and empirical evidence on private entities in Indonesia is quite minimal. This research aims to prove the influence of an ethical code on the risk of asset misappropriation through whistleblowing intentions. The population of this study are employees of medium-scale entities in Jabodetabek and East Java. The sampling method used is purposive. The sample for this research is companies located in Jabodetabek and East Java with employees ranging from 70 to 150 people. This research uses primary data, namely a questionnaire. The researcher tested the validity and reliability of the data through a pilot test. If these two conditions are already met, the data then being analyzed further using path analysis. The data must also meet classical assumptions and linearity testing in path analysis testing. The researcher tested the direct influences using Ordinary Least Square. Meanwhile, the Sobel Test was used to test the indirect influence of the research variables. The Sobel Test results show that whistleblowing intention is proven to mediate the influence of the ethical code on the risk of asset misappropriation. The mediating effect of whistleblowing intention is partial. Whistleblowing intention as a mediator variable has been proven in this research, in line with various previous studies. Because it is proven to mediate partially, the novelty in this research is apart from being a mediator variable, whistleblowing intentions can also be an independent variable, with the risk of asset misappropriation as the dependent variable.